2018
DOI: 10.15447/sfews.2018v16iss3art4
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton Dynamics in the Cache Slough Complex of the Upper San Francisco Estuary

Abstract: We studied abundance and dynamics of zooplankton in the tidal freshwater Cache Slough Complex (CSC) in the northern Delta of the San Francisco Estuary during June, July, and October 2015. We asked whether the CSC was an area of high zooplankton production that could act as a source region for open waters of the estuary. Abundance of the copepod Pseudodiaptomus forbesi was similar to that in freshwater reaches of the central and eastern Delta and higher than that in the adjacent Sacramento River. Growth rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 76 publications
(116 reference statements)
1
17
1
Order By: Relevance
“…S1 b). Prior work in the Cache Slough Complex (stations 4-6) has shown high levels of cyanobacteria DNA and negligible levels of cryptophyte DNA in the guts of P. forbesi, the opposite of what we expected based on their respective abundance and presumed nutritional value (Holmes 2018;Kimmerer et al 2018). Other sequencing-based studies have found cyanobacteria (Synechococcus) to be highly abundant in the guts of C. finmarchicus (Yeh et al 2020).…”
Section: Copepod Dietscontrasting
confidence: 79%
See 1 more Smart Citation
“…S1 b). Prior work in the Cache Slough Complex (stations 4-6) has shown high levels of cyanobacteria DNA and negligible levels of cryptophyte DNA in the guts of P. forbesi, the opposite of what we expected based on their respective abundance and presumed nutritional value (Holmes 2018;Kimmerer et al 2018). Other sequencing-based studies have found cyanobacteria (Synechococcus) to be highly abundant in the guts of C. finmarchicus (Yeh et al 2020).…”
Section: Copepod Dietscontrasting
confidence: 79%
“…This species is also demersal in shallow, clear waters (Kimmerer and Slaughter 2016). A previous study at station 5, the shallowest station, showed day/night differences in abundance of adult females in the 4-m water column (Kimmerer et al 2018), but the mean proportions of P. forbesi females that were ovigerous did not differ between day and night during the three surveys of that study (Kimmerer unpublished). Thus, we are confident that our daytime sampling was unbiased with regard to the proportion of females that were ovigerous and, therefore, the egg production rate.…”
Section: Field Collectionmentioning
confidence: 64%
“…Site differences were largely driven by greater density of cladocerans at the upstream site relative to downstream. Seasonal differences were driven largely by typical species turnover within the San Francisco Estuary (Kimmerer et al, 2018), with calanoid ( Pseudodiaptomus forbesi ) and cyclopoid ( Limnoithona tetraspina ) copepods dominating summer communities and other taxa dominating other seasons (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of zooplankton and nekton within the channel was strongly correlated with the hydrodynamically driven habitat zones described above. The upstream zone characterized by no exchange with downstream habitats supported higher zooplankton densities, and higher densities of Cladocera, a group more abundant in low‐velocity, freshwater habitats regionally (Frantzich et al, 2018; Kimmerer et al, 2018). The downstream, high exchange zone supported the lowest densities of zooplankton, which could reflect low phytoplankton abundance observed in the study or simply the relatively low densities of zooplankton present in many nearby SFE pelagic habitats (Kimmerer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation